G-QFD إمكانية إقامة النشر الأخضر لوظيفة الجودة : دراسة استطلاعية في الشركة العامة للسمنت الشمالية/معمل حمام العليل القديم - احمد هاني محمد النعيمي (PROSPECTIVE RESEARCHES, 2023)
The Green quality function deployment G-QFD is one of the priorities of design teams in the design of the product, in order to achieve satisfaction in terms of quality, cost and environmental requirements. These indicators determine alternatives levels for each requirement of the requirements product concept. This is achieved through collecting them from the house of quality derived from the application of the concept QFD, which represents the quality indicator, and by assessing the costs of internal and external collection gives us an indicator of cost, as well as gives us the indicator of environmental assessment of the impact of the product on the environment. Then compile these indicators in the table for each concept and then choose the product concept, which impairs the best quality and less cost and less impact on the environment, so we got a product that satisfies the customer and the environment together. On this basis, the old Hammam Al-alil cement factory was selected for the search, (46) questionnaire were distributed on three types of each of the department related to a sample of research (quality Dept. & quality control Dept., Department of Environment and Safety Industrial Dept, Accounts Dept). The research shows agreement on the availability of quality index products in the factory, and weaknesses in the remedial action of the waste posed a result of the production process, leading to damage to the ecosystem in the end. as well as, usher find a commitment to the side of the accounts, and this is what led us to provide some of the proposals to the Department of factory, which focused on plant management to take remedial action before the waste as a result of the production process.